Plant tolerance to drought stress: Complexity and mechanism across physiological, molecular and biochemical scales - Batool, Asfa; Yue, Dong-Xia; Xiao, Yun-Li; Li, Shi-Sheng; Duan, Hai-Xia; Haq, Zeeshan; Ahmed, Khalil; Zhao, Ling; Zhu, Li; Xiong, Y.C. (International Journal of Applied and Experimental Biology, 2024)
Drought stress limits crop yield globally and is growing as a result of climate change. Water deficit of soil frequently reduces crop growth and yield regardless of developmental stages and nature of genotypes. There are a variety of mechanisms involved in plants in response to drought stress and they trigger the plant drought tolerance strategies. Plants subjected to drought undergo a sequence of physiological, biochemical, and molecular mechanisms to combat the effects of drought, just like plants exposed to other environmental stressors. Using various methods, researchers are currently attempting to understand the intricate operation of the drought stress response in plants. During particular crucial stages such as seed germination, and formation of seedlings, flowering, and grains, plants are particularly vulnerable to drought stress. Through the activation of tolerance mechanisms, plants successfully mitigate the impacts of drought stress during vegetative development stages. However, drought stress during the generative phase might result in yield losses that are irreversible. The present review highlights the tolerance mechanisms in plants and the functioning of physiological, molecular, and biochemical processes involved in plants’ resistance to water deficit as well as how various crops react to drying conditions at various developmental points.